Assessment of need of effective health education programme for improvement of personal hygiene among adolescent girl students in a slum area of Kolkata: a school based intervention study - Pal, Jayita; Pal, Arghya K. (International Journal of Research in Medical Sciences, 2017)
Background: Personal hygiene aims at healthy living by maintaining cleanliness of the body. Adolescent girls being in the period of active growth and development are the ideal candidates to impart proper knowledge which in turn create a correct attitude followed by practice and it would be carried to next generation. The study aimed to assess the effectiveness of a health education programme in improving the knowledge, attitude and practice of personal hygiene among the adolescent girls in a slum area of Kolkata, West Bengal, India. Methods: A quasi-experimental study was conducted in two government Bengali medium secondary schools located in a slum area of Kolkata, West Bengal, India. First a baseline survey with the help of a predesigned pretested questionnaire and checklist was done to find out the socio-demographic information and existing K.A.P of personal hygiene of the students. This was followed by an intervention phase of 6 months during which weekly lecture and demonstration classes were taken in the study school. Impact of intervention was assessed by application of post-test questionnaire. Both the schools were followed for another 3 months to establish the sustainability of the programme. Results: There was statistically significant improvement in the mean scores of K.A.P of personal hygiene from the pre-test level to post-test level among the students of study school as compared to control school, though there was a significant decline in the mean scores at 9 months than 6 months revealing want of sustainability of the programme. Conclusions: Regular revision and reinforcement should be done to increase the effectiveness of a health education programme to improve personal hygiene and thereby resulting in a healthy living.